Experimental Investigation of Wear Resistance in Engineering Ceramics (Strojniški vestnik – Journal of Mechanical Engineering, 2016)
This study experimentally investigates the wear resistance of advanced engineering ceramics under abrasive operating conditions. Mechanical testing was performed to evaluate friction behavior and material degradation. The results demonstrate excellent wear performance for industrial applications.
Keywords: Engineering ceramics; Wear resistance; Material testing; Surface properties; Mechanical engineering